Reaction of Bipolaris euphorbiae to environmental factors and its tolerance to solar and ultraviolet radiation - Moraes, Carime [UNESP]; Monteiro, Antonio Carlos [UNESP]; Mochi, Dinalva Alves [UNESP] (Springer, 2011)
The determination of the ideal cultivation conditions and the knowledge of solar radiation tolerance are important aspects that must be investigated for the use of Bipolaris euphorbiae Muchovej and Carvalho as a biocontrol agent. The present study was done to assess the growth rate, sporulation and viability of the fungus cultivated under different conditions of the initial pH value of the growth medium, temperature and photoperiod. The tolerance of this fungus' conidia to light from a source simulating solar and ultraviolet radiation was also assessed. B. euphorbiae was affected by different pH values of the growth medium being 6.0 the adequate pH for fungus cultivation. Incubation of the fungus under temperatures of 22, 25 and 28A degrees C enhanced mycelium growth, while sporulation and viability of conidia were better at 22 and 16A degrees C. Different regimens of exposure to light of fungal cultures only affect sporulation. Conidia exposed to solar and ultraviolet radiation for 8 h and 90 min, respectively, presented viabilities higher than 92%, indicating high tolerance levels to radiation exposure.
Keywords: Phytopathogenic fungus; Biological control; pH; Temperature; Light exposure; Radiation